The Implementation of Personal Photograph as Media in Writing Descriptive Text at SMP Negeri 3 Sungguminasa - Nurul Aulia Dewi; Haryanto Atmowardoyo; Kisman Salija (Har Press Indonesia, 2022)
This research aims to find out whether personal photograph improve significantly the students’ skill in writing descriptive text and to find out students’ perception on the implementation of personal photograph in writing descriptive text. In this research, the population is the eighth-grade students. The research design used in this research was quasi-experimental design. The sample was taken two classes, one class as the experimental class, VIII C and the other class as the control class, VIII D. In collecting the data, the researcher used the instrument in the form of writing test for pre-test and post-test. The results of this research found that value of the t-test was 3.633 and the value of the t-table was 1.734 with significant level (P) = 0.05 and (df) = 20, then the value of t-test was higher than the value of t-table (3.633 > 1.734). It means that H1 > HO, the hypothesis was accepted. Then, the result questionnaire, question number 1-10 showed that almost all of students agree that personal photograph helps them in writing descriptive text.